Civil Engineering Projec Management - TWORT, Alan C (Elsevier, 2004)
This new edition of Civil Engineering: Supervision and Management updates and revises the best practical guide for on-site engineers. Written from the point of view of the project engineer it details their responsibilities, powers and duties.